Uncertainty in Health Emergencies: Communicating Risks During COVID-19 Response - Logar, Silvia; Bednarova, Rym; Rizzardo, Alessandro; Miceli, Luca (Frontiers in Communication, 2022)
The world's fragmented response to the COVID-19 pandemic created fertile ground for mixed messages and inconsistency. authors analyzed Google trending insights from five Countries (Italy, Spain, USA, UK and France) across three-week time (1 to 23 March 2020) to document trends in population health anxiety in response to the initial global spreading of the outbreak. The results are expressed in form of “Uncertainty Index (UI)”, which reflects the total number of Google searches/COVID-19 prevalence and standardized per million inhabitants. The United Kingdom experienced the highest level of the health anxiety (UI= 11,5), followed by France (UI=4,6) and Spain (UI=3,2). United States suffered overall the highest rate of uncertainty in the early stage of pandemics; Italian population experienced a balanced level of anxiety. Institutionalizing risk communication during COVID-19 should represent an integral part of the Country emergency response.